Group Support's Effect on Stigma Reduction and Medication Adherence Improvement among HIV-Positive Individuals - Adistha Eka Noveyani; Triska Dwi Cahyani; Khoirunnisa Yunita; Anis Latifah; Mochammad Farhan Maulana; Yee Bit Lyan (Talenta Publisher, 2024)
An effort to reduce stigma and discrimination is still a challenge in controlling HIV cases and improving adherence to the medication among People Living with HIV (PLHIV). This study aimed to determine the factors that reduce stigma and discrimination in healthcare facilities. This research employed a mixed-method study. The population was HIV/AIDS patients in the Puger and Kencong areas. The sampling technique was purposive sampling, which resulted in 30 respondents. The variables included the level of discrimination, medication adherence, and stigma reduction strategies. Quantitative data were analyzed descriptively, and qualitative data were analyzed by content analysis. The level of discrimination felt by PLHIV is 100%, which is low. While the level of adherence to taking medication for the majority of PLHIV is classified as high (69.7%). The success in reducing stigma and discrimination in health services was influenced by the accompanying factor of PLHIV, in which peer support always accompanied PLHIV in carrying out medication, helping to take ARV when PLHIV was unable to visit the healthcare facility, and mingling with PLHIV so PLHIV felt less alone. The research indicates that implementing peer support programs in the Jember District has significantly reduced discrimination in healthcare services and improved treatment adherence among PLHIV. It was proven by high adherence to taking medication and the low level of discrimination experienced by PLHIV. Suggesting that similar models could enhance public health outcomes in other regions.